(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Sexuality, as an instinctive and basic human need, is an important part of the whole life cycle and a key topic at the stage of healthy development of minors. This paper observes the situation encountered in the development of sexual education for minors in the family, school and society. It analyzes the national law’s view on the age of sexual consent of minors from the perspective of respecting and protecting the sexual rights of minors. Based on this, it proposes an optimization strategy for sex education for minors, namely, sex education for minors based on social-emotional learning theory. Further propose the optimization strategy and practice method of comprehensive sex education for minors based on social-emotional learning theory. Analyze the current cognitive level of minors’ sexual cognition, sexual attitude and sexual behavior, and predict the prediction rate of the occurrence of risky sexual behavior. Comparative experiments are set up to analyze the realistic role of comprehensive sex education interventions. In the analysis of the incidence of risky sexual behaviors, the results of the comprehensive minors’ incidence of risky sexual behaviors showed that for all kinds of risky sexual behaviors of minors, the number of males was higher than that of females. And male, age >16, migration experience, relationship experience, identification with extramarital sex, identification with one-night stand, identification with one-time sex without condom are the risk factors for sexual behavior.